Bicycle thieves - De Sica, Vittorio, 1901-1974; Maggiorani, Lamberto, 1910-1983; Staiola, Enzo, 1939-; Carell, Lianella, 1927-; Bartolini, Luigi, 1892-1963 ([New York, N.Y.] : Criterion Collection, 2007)
In postwar, poverty-stricken Rome, a man and his son set to look for his stolen bicycle which is his only means of making a living.
Based on the novel by Luigi Bartolini.
Originally released as a motion picture in 1948.
Features: "Working with De Sica," a collection of new interviews with screenwriter Suso Cecchi D'Amico, actor Enzo Staiola, and film scholar Callisto Cosulich, "Life as it is," a new program on the history of Italian neorealism in cinema with scholar Mark Shiel, documentary on screenwriter and longtime Vittorio De Sica collaborator Cesare Zavattini, directed by Carlo Lizzani.
Lamberto Maggiorani, Enzo Staiola, Lianella Carell, Gino Saltamerenda, Vittorio Antonucci, Giulio Chiari.
MPAA rating: Not rated.
DVDs, Dolby digital mono.
Keywords: Bartolini, Luigi, -- 1892-1963 -- Film and video adaptations; Bicycles -- Drama; Unemployment -- Italy -- Drama; Fathers and sons -- Italy -- Drama; Poor families -- Italy -- Drama; Italy -- Social conditions -- 20th century -- Drama; Motion pictures, Italian; Based on the book; Feature films; Foreign films